Analysis of Factors Influencing ICAO English Language Proficiency of Air Traffic Controllers at Jakarta ATSC - Clara Sinta Gundani; Nunuk Praptiningsih; Gilang Trio Putra (CV. AFDIFAL MAJU BERKAH, 2026)
This study aims to analyze the factors influencing the level of ICAO English language proficiency among Air Traffic Controllers (ATCs) at Jakarta Air Traffic Service Centre (JATSC). English proficiency is a critical requirement to ensure effective communication, safety, and efficiency in air traffic operations as mandated by the International Civil Aviation Organization (ICAO). This research employs a quantitative approach with a causal associative design. Data were collected through structured questionnaires distributed to 92 active ATCs at JATSC. The independent variables examined include frequency of English usage, work experience, English language training, and learning motivation, while ICAO English proficiency serves as the dependent variable. The data were analyzed using descriptive statistics and multiple linear regression analysis to identify both partial and simultaneous effects of the independent variables. The results show that all examined factors significantly influence ICAO English proficiency, both individually and collectively. Among these variables, work experience and frequency of English usage have the strongest effect on proficiency levels. The study concludes that ICAO English proficiency is influenced not only by formal training, but also by consistent operational practice, accumulated professional experience, and strong individual motivation. These findings emphasize the importance of continuous language exposure and integrated competency development programs to support aviation safety.